Comparison of High-Throughput Sequencing Methods for Monitoring Genetic Changes in Ebolavirus Populations - Nagle, Elyse R. (My University, 2017)
Amplicon-based sequencing of Ebolavirus is a powerful tool to monitor the genetic changes in the viral population during a drug study. Short amplicons are generated covering the whole virus genome and a library is generated and sequenced. This method can detect complete Ebolavirus in samples with only 105 genome copies/mL, but it is time-consuming and requires extensive PCR, potentially producing errors. A new Ebolavirus-targeted capture and enrichment method, RNA Access was used to increase the sensitivity of detection and reduce PCR error. The two methods were compared with the same set of samples. Surprisingly, RNA Access is not as sensitive and the amplicon-based method; complete Ebolavirus genomes were sequenced from 106 genome copies/mL and required more sequencing reads than the amplicon-based method. Despite these shortcomings, the protocol speed and minimal PCR make RNA Access a viable method to monitor genetic variation in an Ebolavirus population.
Keywords: Amplicon sequencing; Ebolavirus; Next Generation Sequencing; Population genetics; SNPs; Target Capture